Food insecurity and its predictors among lactating mothers in North Shoa Zone, Central Ethiopia: a community based cross-sectional study. Issue 11 (20th November 2020) - Getacher, Lemma; Egata, Gudina; Aynalem, Yared Asmare; Molla, Abebaw; Tesfaye, Adane; Abebe, Haimanot; Bayih, Wubet Alebachew; Habtegiorgis, Samuel Derbie
Abstract : Objective: To assess the prevalence of food insecurity (FI) and its predictors among lactating mothers in Ataye District, North Shoa Zone, Central Ethiopia. Design: A community-based cross-sectional study design was used. Setting: Two urban and four rural randomly selected kebeles of the Ataye District in Ethiopia. Participants: Out of 635 participants, 612 lactating mothers aged 15–49 years participated from February to April 2018. Mothers who lived for at least 6 months and above in the district were included, and mothers who were not able to respond to an interview were excluded. A single lactating mother per household was included. Lactating mothers in the households were selected using a cluster sampling technique. The number of lactating mothers found in each kebele was taken from family folder documentation. Primary outcome: The prevalence and predictors of food insecurity. Results: The prevalence of FI among lactating mothers was 36.8%. No formal education (adjusted OR (AOR) =1.82, 95% CI 1.13 to 2.92), no income-generating activities (AOR=3.39, 95% CI 2.05 to 5.64), no home gardening practice (AOR=5.65, 95% CI 3.51 to 9.08), alcohol use by husbands (AOR=2.02, 95% CI 1.25 to 3.24), low minimum dietary diversity score (AOR=2.94, 95% CI 1.88 to 4.57), less than three frequencies of meals (AOR=3.97, 95% CI 1.65 to 9.54) and three meals only per day (AOR=1.86, 95% CI 1.08 to 3.17) were significant predictors of FI of mothers. Conclusion: The prevalence of FI was high in the study area. No formal education, no income-generating activities, no home gardening practice, alcohol use by husbands, low minimum dietary diversity score, fewer than three frequencies of meals and three meals only per day were independent predictors of FI. Therefore, increasing home gardening, decreasing alcohol intake, increasing dietary diversity and performing income-generating activities are highly recommended to reduce FI.